ANALISIS PENERAPAN GOOD GOVERNANCE PADA ALOKASI DANA DESA DI DESA HUTAPAUNG KECAMATAN POLLUNG KABUPATEN HUMBANG HASUNDUTAN - Lumban Gaol, Rey Fantri; Purba, Imelda Rimenda (UNIKA Santo Thomas, 2025)
This study aims to find out whether the implementation of good governance in the Village Fund Allocation in Hutapaung Village, Pollung District, Humbang Hasundutan Regency in 2021-2023 has been carried out in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018. The population of this study is the Village Revenue and Expenditure Budget Realization Report in Hutapaung Village, Pollung District, Humbang Hasundutan Regency. The sample of this study is the Village Revenue and Expenditure Budget Realization Report in Hutapaung Village, Pollung District, Humbang Hasundutan Regency for 2021-2023. The research methods used were documentation, interviews, and questionnaires. The data analysis technique used is a descriptive data analysis technique. The results of this study show that the implementation of Good Governance in Village Fund Allocation in Hutapaung Village, Pollung District, Humbang Hasundutan Regency in 2021-2023 is not optimal. Because in the principle of transparency, it is still difficult for the public to obtain information related to the report on the realization of the implementation of the Village Fund Allocation. In principle, participation does not involve the community directly during the planning of the management of the Village Fund Allocation. The suggestions that can be given are the need to provide information media that is easily accessible to the community related to the report on the realization of the implementation of the APBDes, involving the village community during the planning of the management of the Village Fund Allocation so that there is an opportunity for ideas from the community, and managing the Village Fund Allocation in accordance with Permendagri Number 20 of 2018.